Neutralizing and Epitope-Specific Antibodies against Respiratory Syncytial Virus in Maternal and Cord Blood Paired Samples - Fumi Mashiyama; Koichi Hashimoto; Sakurako Norito; Hisao Okabe; Akiko Sato; Yohei Kume; Ryo Maeda; Maki Sato; Masatoki Sato; Hyo Kyozuka; Keiya Fujimori; Hidekazu Nishigori; et al. (Viruses, 2022)
Only a few qualitative studies of neutralizing antibody titers (NATs) against respiratory syncytial virus (RSV) have focused on epitope-specific antibody (ESA) levels. Here, NATs against RSV in sera were measured using the blood of 412 mothers and cord blood (CB) of 95 of the 412 mother–child pairs. ESA levels against sites zero (Ø) and IIa of the F protein of RSV were measured in 87 of the 95 mother–child pairs. The median gestational age was 39 weeks. The NATs and ESA levels in CB were slightly higher than those in maternal blood (MB). The NATs for RSV subtype A (RSV-A) in MB and CB showed a positive correlation (r = 0.75). The ESA levels against sites Ø and IIa in MB and CB showed positive correlations, r = 0.76 and r = 0.69, respectively. In MB, the NATs and ESA levels against RSV were positively correlated, more significantly against site Ø (RSV-A: r = 0.70, RSV-B: r = 0.48) than against site IIa (RSV-A: r = 0.19, RSV-B: r = 0.31). Sufficient amounts of ESAs against sites Ø and IIa of RSV were transferred from mothers to term infants. ESA levels against site Ø contribute to NATs.